Mathematical modeling of thin‑layer drying of fermented grape pomace - Ferreira, Luiz Fernando Dias; Pirozi, Mônica Ribeiro; Ramos, Afonso Mota; Pereira, José Antonio Marques (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the drying characteristics of fermented grape pomace in a hot air‑dryer, to evaluate the descriptive capacity of known mathematical models of thin‑layer drying, and to establish the values of effective diffusivity and activation energy. Drying experiments were conducted at 50, 60, 70, 80 and 90ºC, with 1.0 m s-1 air‑drying velocity. Ten different mathematical models for thin‑layer drying were compared, according to the values of coefficient of determination (R2), chi‑square (χ2), residual mean square root (RMSR), and relative mean error (P) estimated by the drying curves. The effects of drying temperature on the coefficients and constants were predicted by the regression models. The modified Page model was selected to represent the behavior of thin‑layer drying of grape pomace. The mean values of effective diffusivity varied from 1.0091 x 10-9 m2 s-1 to 3.0421 x 10-9 m2 s-1, at the evaluated temperatures. Effective diffusivity dependence on temperature was described by the Arrhenius equation, with activation energy of 24.512 kJ mol-1.